Successful Treatment of Primary Sjogren's Syndrome Associated with Interstitial Lung Disease - Laniyati Hamijoyo; Kevin Yonatan Budiman; Reza Kurniawan Tanuwihardja (Indonesian Rheumatology Association, 2020)
We report a rare case of interstitial lung disease as the first clinical manifestation of primary Sjögren’s syndrome. A 49-year-old woman was assessed, complaining of dyspnea, dry cough, dry mouth, inflamed right cheek, dry skin, bilateral gastrocnemius pain, multiple peripheral arthralgia, and generalized weakness for the previous 2 months. Serology examination was positive for Sjögren’s syndrome antibodies. Thorax CT demonstrated Crazy Paving appearance. Glucocorticoid alone did not improve the respiratory symptoms, hence azathioprine was given. Subsequent dyspnea regression and disease control obtained after 5 months of therapy. This case demonstrated that ILD could be the first clinical manifestation in pSS, and azathioprine could be used as the first line therapy for Sjögren’s syndrome-related lung disease.